Crime prevention through environmental design and fear of crime : case study on landed residential areas in Putrajaya - Mohamad Sabri Mokhtar (Kulliyyah of Information Technology and Communication, International Islamic University Malaysia, 2019)
Crime Prevention through Environmental Design (CPTED) promotes that physical environment can be used to produce behavioral effects that will reduce the incidence and fear of crime, thus improving quality of life. This approach is important to manifest Safe City Programme especially in Malaysia. Putrajaya as administration centre allows non-gated residential in it areas and adopts safe city practice since 2004. However, this approach is still questionable due to the frequent occurrence of crime that has been reported in Putrajaya particularly in certain precincts involving landed residential areas. Therefore, the aim of this research is to examine the residents' implementation on CPTED and perception on FOC in the different landed residential areas at Putrajaya. Case study by deployed an observation on CTED practices and a survey on residents' attitudes on CPTED and fear of crime (FOC) in individual non-gated landed housing areas were conducted in Precincts 8, 9, 10 and 11 in Putrajaya. Analysis of the result indicated that Precincts 10 and 11 attained high level on CPTED practices, while Precincts 8 and 9 attained moderate level on CPTED practices. In term of attitudes on CPTED, Precincts 9, 10 and 11 indicated high level whereas moderate level indicated by Precinct 8. Precincts 9 and 11 indicated high level on FOC, whereas Precincts 8 and 10 indicated moderate level on FOC. There is no relationship between attitudes on CPTED and FOC in Precincts 8, 9 and 10 except the relationship only exist in Precinct 11. Recommendations included improvement on all aspects of territoriality, access control by alarm installation and other additional related measures, surveillance by ensuring that there is no garden element that can be a space for criminals to hide, maintenance and target hardening by repainting faded exterior paint of the house, and to design educational programs in order to increase CPTED implementation awareness in government quarters. Future studies are recommended to expand sample and population in Putrajaya to other related precincts, comparison between government servant and non-government servant in Putrajaya, and to continue this study to the high-rise residential areas in Putrajaya.